Paeonol Derivatives and Pharmacological Activities: A Review of Recent Progress - Wang, Jilei; Wu, Guiying; Chu, Haiping; Wu, Zhongyu; Sun, Jingyong (Mini Reviews in Medicinal Chemistry, 2020)
Paeonol, 2-hydroxy-4-methoxy acetophenone, is one of the main active ingredients of traditional Chinese medicine such as Cynanchum paniculatum, Paeonia suffruticosa Andr and Paeonia lactiflora Pall. Modern medical research has shown that paeonol has a wide range of pharmacological activities. In recent years, a large number of studies have been carried out on the structure modification of paeonol and the mechanism of action of paeonol derivatives has been studied. Some paeonol derivatives exhibit good pharmacological activities in terms of antibacterial, anti-inflammatory, antipyretic analgesic, antioxidant and other pharmacological effects. Herein, the research progress on paeonol derivatives and their pharmacological activities were systematically reviewed.
Keywords: antitumor